First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia - Yasunaga, Tomohide; Yamada, Kazutaka; Soe, Zayar; Naing, Shine Shane (Zootaxa, 2016)
Two oriine flower bug (Hemiptera: Heteroptera: Anthocoridae) genera, Bilia Distant, 1904 and Wollastoniella Reuter, 1884 are reported from Myanmar for the first time, diagnosed, and discussed. A new species, Bilia burma Yasunaga & Yamada sp. nov., is described, with information on the immature form, habitat and assumed prey; its closest sister species, B. castanea (Carvalho, 1951), is also re-diagnosed. Wollastoniella rotunda Yasunaga & Miyamoto, 1993 originally described from northern Thailand, is also documented along with its immature form and new host association. Both of the anthocorids found in Myanmar co-occurred with lace bugs (Tingidae). A checklist of all current members of Bilia and Wollastoniella is provided. The phylogenic positions of Bilia and Wollastoniella in the tribe Oriini is discussed.